Pengaruh Program Film Literasi terhadap Minat Kunjungan di Dinas Perpustakaan dan Kearsipan Kabupaten Pesisir Selatan - Sari, Fuji Wandan; Marlini, Marlini (Lembaga Yasin AlSys, 2025)
The decline in public interest in visiting libraries, driven by the convenience of digital access, presents a strategic challenge for public libraries, particularly the Office of Library and Archives of Pesisir Selatan Regency. In response to this challenge, the library launched an innovative program titled Layanan Digital Film Literasi dan Inklusi Sosial (Lagi Firal). This study aims to analyze the impact of the literacy film program on user visit interest. A descriptive quantitative approach was employed, with the study population consisting of visitors participating in the film literacy program. A sample of 94 respondents was determined using the Slovin formula and purposive sampling technique. The research instrument was a Likert-scale questionnaire that had been tested for validity and reliability. Data were analyzed using descriptive statistics, correlation tests, simple linear regression, and the coefficient of determination with the aid of SPSS version 25. The findings indicate that the film literacy program has a positive and significant effect on visit interest, with a significance value of 0.000 (< 0.05) and a contribution of 42.2%. The entertainment and enjoyment indicators received the highest scores, suggesting that educational films successfully create a positive and enjoyable library experience. The study concludes that the literacy film program is effective in increasing public interest in visiting libraries and recommends its continued development through content diversification and broader, adaptive promotional strategies.